2017
DOI: 10.3390/safety3010005
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Inhibits Organic Dust-Induced ICAM-1 Expression on Bronchial Epithelial Cells

Abstract: Aims: Exposure to dusts/bioaerosols in concentrated animal feeding operations (CAFOs) results in inflammatory lung diseases in workers. Hog CAFOs dust extract (HDE) increases expression of intercellular adhesion molecule-1 (ICAM-1), neutrophil adhesion, and TNFα release in bronchial epithelial cells. Alcohol consumption is increasingly recognized to impair lung immunity. We hypothesized that alcohol impairs HDE-induced TNFα, ICAM-1 expression and neutrophil adhesion by directly inhibiting TNFα converting enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Future studies are warranted using this model to assess not only total recellularization capacities of BEC within the context of DE but to specifically address changes in both cellular attachment as well as cellular growth changes associated with DE challenge. We have previously found that DE treatment causes changes in cell adhesion molecule expression, growth and migration (26,27,44,58), supporting these future investigations. Studies specifically addressing attachment and growth of cells in the large-airway extracellular matrix (ECM; e.g., Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Future studies are warranted using this model to assess not only total recellularization capacities of BEC within the context of DE but to specifically address changes in both cellular attachment as well as cellular growth changes associated with DE challenge. We have previously found that DE treatment causes changes in cell adhesion molecule expression, growth and migration (26,27,44,58), supporting these future investigations. Studies specifically addressing attachment and growth of cells in the large-airway extracellular matrix (ECM; e.g., Fig.…”
Section: Discussionsupporting
confidence: 74%
“…It is important to note other studies have shown that HBECs exposed to 20% CSE for 48 h or 5% CSE for 24 h do not have an increase in LDH [ 24 , 25 , 26 , 27 , 28 ]. In addition, we have shown in many of our previous studies that 100 mM ethanol does not increase LDH [ 29 , 30 , 31 , 32 , 33 ]. Therefore, since we exposed the cells to 5% CSE and/or 50 mM ethanol for 1 h in this study, we do not expect the treatments alone in the absence of the virus to have any effect on LDH activity in HBECs.…”
Section: Resultsmentioning
confidence: 88%
“…Research has shown that TNF-α can induce ICAM-1 antigen expression on the surface of umbilical vein endothelial cells causing vascular endothelial dysfunction. Moreover, studies have shown that ICAM-1 is not expressed on the surface of normal endothelial cells [15]. Therefore, ICAM-1 can be used to target genes to inflammatory sites for ultrasound imaging studies.…”
Section: Discussionmentioning
confidence: 99%